1997
DOI: 10.1111/j.1502-3885.1997.tb00649.x
|View full text |Cite
|
Sign up to set email alerts
|

The Storegga tsunami along the Norwegian coast, its age and run up

Abstract: 1997 (March): The Storegga tsunami along the Norwegian coast, its age and runup. Boreas, VoI. 26, pp. 29-53. OSIO. ISSN 0300-9483.The statigraphy in 25 coastal lakes shows that most of the Norwegian coastline was impacted by a large tsunami about 7200 I4C BP. The methodology has been to core a staircase of lake basins above the contemporary sea level in several areas and to map the tsunami deposit to its maximum elevation. The tsunami was identified in the sedimentary record as an erosional unconformity overla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
98
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 196 publications
(102 citation statements)
references
References 16 publications
3
98
0
Order By: Relevance
“…This weighted average (7308 ± 28 14 C-BP: 8110 ± 50 calBP) corresponds closely to the date of 7300 14 C-BP (8150 calBP) proposed by Bondevik et al (1997) and Bondevik et al (2003), but disagrees significantly with the result of 8350 calBP obtained by Boomer et al (2007). If the Boomer et al (2007) estimate is correct, then the dating discrepancy poses the question of whether both studies are addressing the same event, and notably whether the event observed at Howick indeed represents the Storegga Slide tsunami.…”
Section: England (Howick Case Study)mentioning
confidence: 86%
See 3 more Smart Citations
“…This weighted average (7308 ± 28 14 C-BP: 8110 ± 50 calBP) corresponds closely to the date of 7300 14 C-BP (8150 calBP) proposed by Bondevik et al (1997) and Bondevik et al (2003), but disagrees significantly with the result of 8350 calBP obtained by Boomer et al (2007). If the Boomer et al (2007) estimate is correct, then the dating discrepancy poses the question of whether both studies are addressing the same event, and notably whether the event observed at Howick indeed represents the Storegga Slide tsunami.…”
Section: England (Howick Case Study)mentioning
confidence: 86%
“…In one case, a radiocarbon age was obtained on a stick immediately above the sand layer. Following critical sample selection, Bondevik et al (1997) propose that the tsunami most likely dates to c. 7300 14 C-BP. This age is supported by Bondevik et al (2003), who give a calibrated age value of c. 8150 calBP.…”
Section: Norwaymentioning
confidence: 99%
See 2 more Smart Citations
“…Paleotsunami deposits are often identified in lowenergy coastal environments, such as tidal marsh, back-barrier marshes and coastal lakes. Most publications on paleotsunami studies during the past two decades are from temperate zones such as the north Atlantic (Bondevik et al, 1997;Bondevik et al, 2003;Dawson et al, 1988), the circum-Pacific shores of the Americas and Asia (Atwater & Moore, 1992;Atwater et al, 2005;Bourgeois et al, 2006;Cisternas et al, 2005;Fiedorowicz & Peterson, 2002;Kelsey et al, 2005;Minoura & Nakata, 1994;Nanayama et al, 2003;Tuttle et al, 2004) Goff et al, 2001;Goff et al, 1998;Grauert et al, 2001). In many cases tsunami studies occur in conjunction with other evidence for large earthquakes such as the study of coastal geological evidence of past tsunamis and associated post seismic uplift in Japan by Sawai et al (2009b).…”
Section: Background Research In Paleotsunami Studymentioning
confidence: 99%